Eficácia do tetra-test como ferramenta de gestão da qualidade do leite cru refrigerado - De Oliveira, Camilo Ferreira [UNESP]; Da Costa Machado, Rodolpho [UNESP]; Da Costa Barbon, Ana Paula Ayub [UNESP]; Prata, Luiz Francisco [UNESP] (FapUNIFESP (SciELO), 2012)
The effectiveness of a new management tool for screening refrigerated raw milk quality in a dairy industry is provided. Three hundred and seventy-four samples of raw milk from individual producers and 125 samples from bulk milk carriers from the same producers were analyzed. Producers' samples underwent a fast tube reduction test, or Tetra-Test, to estimate total bacteriological charge and their predominant microbiota. Bulk milk samples underwent standard plate count (SPC) as reference method. Tetra-test was effective in screening and assessing the microbiological quality of refrigerated raw milk, since 82.4% of samples with more than 106UFC/mL were readily detected (5 minutes to 2h). The test may be employed as a management tool either in screening or in interventions on the detected problem. In fact, its results provided complementary information on the characteristics of dominant microbiota. Most samples failed in compliance to IN 51 requirements. Further, 211 samples (56.4%) showed high microbial charge and, consequently, poor quality raw milk. Psychrotrophic groups were not yet the main degrading factors of cooled raw milk, albeit present in 76.8% of samples.
Effectiveness of tetra-test as a tool for quality management of refrigerated raw milk
Keywords: Psychrotrophic groups; Quality; Quality management; Refrigerated raw milk; Tetra